The inherently (un)just real property tax - Pelikánová MacGregor, Radka; Jánošíková, Petra (Research Papers of Wrocław University of Economics, 2018)
The aim of this paper is to research, analyse and comparatively assess the real property tax and it´s Aristotelian (in)justice in various jurisdictions based on the stated quartet of hypotheses. Considering the high focus of jurisdictions on both sides of the Atlantic on human rights and democracy, it is highly relevant to pose the question centred around the hypotheses that (i) real property taxation, (ii) determination of basis, (iii) calculation and rate and (iv) use of proceeds of real property tax are (in)compatible with our perception of justice as founded by Aristotle. Various jurisdictions are analysed, while particular attention given to the Czech Republic jurisdiction case study. The research allows to enhance the understanding and appreciation of the real property tax system and offers preliminary suggestions and recommendations for its improvement in order to make it an effective, efficient and just fiscal tool matching the post-modern global society
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 146-159
Keywords: real property tax; justice; basis; rate; calculation; podatek od nieruchomości; sprawiedliwość; podstawa opodatkowania; stawka podatku; obliczanie